COMMERCIALIZATION OF AGRIFOOD PRODUCTS THROUGH PNAE AND PAA: A STUDY WITH SMALLHOLDER FARMERS IN PARANÁ, BRAZIL - Bánkuti, Sandra Mara Schiavi; Culti, Maria Nezilda; Guimarães, Amanda Ferreira; Cezar, Arthur de Canini; Pinto, Gheysa Julio (Informe GEPEC, 2019)
Commercialization has been highlighted as one the main obstacles for farmers in Brazil. Public policies have encouraged smallholder farmers to increase commercialization through institutional markets, named National School Feeding Program (PNAE) and Food Acquisition Program (PAA). The aim of this paper is to analyze commercialization of agrifood products by smallholder farmers in Paraná, Brazil, including PNAE and PAA programs. Empirical research comprised primary data from interviews with 27 smallholders in Paiçandu, Paraná. Results indicated that most farmers participate individually of PNAE and PAA, and main products are vegetables and processed products. Main advantages of PAA and PNAE are the assurance of sale, followed by prices. Main difficulties concern scale and assurance of supply, besides relative prices, especially for those accessing short channels. Collective actions would help farmers to overcome difficulties, and create opportunities for developing other channels, such as collective street markets.